Culture and Business Ethics – A Comparative Perspective (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
Accelerating growth in business globalization places managers in an international environment with more ethical challenges. Ethical principles that govern businesses in a particular culture may not match with the conditions, norms and customs of other cultures. The article aims to examine comparatively the role of culture in explaining ethical issues and dilemmas in organizations. Treating the issue of business ethics in companies nowadays offer different perspectives depending on the influence of the cultural context of countries where these companies operate. Each cultural context shows its specificity, in addition to legal regulations, customs, habits or moral issues, which deserve to be highlighted in a paper on how to conduct business from an ethical perspective.